HIV and respiratory illness in the antiretroviral therapy era - Jaffer, Amina; Devani, Nikesh; Brown, James; Mandal, Swapna; Lipman, Marc (Annals of Research Hospitals, 2017)
Respiratory illness is a common manifestation of HIV infection. The availability of effective antiretroviral therapy (ART) has changed the pattern of respiratory ill-health experienced by people living with HIV (PLWH). Among populations with good access to ART, opportunistic respiratory infections such as Pneumocystis jirovecii pneumonia (PCP) are becoming less frequent. However, there is evidence to suggest that these populations may be at greater risk of serious non-AIDS illness including chronic respiratory disease. Although there is remaining uncertainty about the extent to which HIV represents an independent risk-factor for respiratory illness in individuals with a suppressed HIV viral load and immune reconstitution, in many settings PLWH have greater exposure to risk factors for respiratory illness (in particular tobacco smoking), which contribute to this burden of disease. As HIV-positive populations age, management of these conditions will therefore become increasingly important. Healthcare services need to manage this growing burden of chronic respiratory illness and provide access to preventative measures including smoking cessation and immunisation against vaccine-preventable respiratory infections in a way that is appropriate to the populations served.